Adverse Childhood Experiences Predict Early Initiation of Opioid Use Behaviors - Guarino, Honoria; Mateu-Gelabert, Pedro; Quinn, Kelly; Sirikantraporn, Skultip; Ruggles, Kelly V.; Syckes, Cassandra; Goodbody, Elizabeth; Jessell, Lauren; Friedman, Samuel R. (Frontiers in Sociology, 2021)
Introduction: Although a substantial body of research documents a relationship between traumatic stress in childhood and the initiation of substance use later in the life course, only limited research has examined potential linkages between adverse childhood experiences (ACEs) and the initiation of nonmedical prescription opioid use and other opioid use behaviors. The present study contributes to this growing body of work by investigating the association of childhood trauma with early initiation of a series of opioid use behaviors. Methods: New York City young adults (n=539) ages 18-29 who reported nonmedical use of prescription opioids or heroin use in the past 30 days were recruited using Respondent-Driven Sampling in 2014-16. Ten ACEs were assessed via self-report with the ACE Questionnaire. Associations between number of ACEs and self-reported ages of initiating seven opioid use behaviors (e.g., nonmedical prescription opioid use, heroin use, heroin injection) were estimated with multivariable logistic regression. Results: 89% of participants reported at least one ACE, and 46% reported four or more ACEs, a well-supported threshold indicating elevated risk for negative health consequences. Every increase of one trauma was associated with a 12-23% increase in odds of early initiation across the seven opioid use behaviors. Findings also document that the mean age at initiation increased with increasing risk severity across the behaviors, contributing to evidence of a trajectory from opioid pill misuse to opioid injection. Discussion: Increasing number of childhood traumas was associated with increased odds of earlier initiation of multiple opioid misuse behaviors. In light of prior research linking earlier initiation of substance use with increased substance use severity, present findings suggest the importance of ACEs as individual-level determinants of increased opioid use severity. Efforts to prevent onset and escalation of opioid use among at-risk youth may benefit from trauma prevention programs and trauma-focused screening and treatment, as well as increased attention to ameliorating upstream socio-structural drivers of childhood trauma.